KONTROVERSI MAKNA DAN KONSEP JIHAD DALAM ALQURAN TENTANG MENCIPTAKAN PERDAMAIAN - Deni Irawan (Religi: Jurnal Studi Agama-agama, 2014)
The word jihad is inter preted in various meaning. Some inter prets it in a nega- tive and destructive connotations, others inter pret it as noble actions. The de- bate on the meaning of jihad are endless as long as there is no clear definition and restrictions which actions are considered as jihad and which ones are not. In order to find the true meaning of jihad, this paper examines the word jihad, both from the Qur’anic perspective and academia discourses.